Acetyl-CoA Carboxylases and Diseases - Wang, Yu; Yu, Weixing; Li, Sha; Guo, Dingyuan; He, Jie; Wang, Yugang (Frontiers in Oncology, 2022)
Acetyl-CoA carboxylases (ACCs) are enzymes that catalyze the carboxylation of acetyl-CoA to produce malonyl-CoA. In mammals, ACC1 and ACC2 are two members of ACCs. ACC1 localizes in the cytosol and acts as the first and rate-limiting enzyme in the de novo fatty acid synthesis pathway. ACC2 localizes on the outer membrane of mitochondria and produces malonyl-CoA to regulate the activity of carnitine palmitoyltransferase 1 (CPT1) that involves in the β-oxidation of fatty acid. Fatty acid synthesis is central in a myriad of physiological and pathological conditions. ACC1 is the major member of ACCs in mammalian, mountains of documents record the roles of ACC1 in multiple diseases, such as cancer, diabetes, obesity. Besides, acetyl-CoA and malonyl-CoA are cofactors in protein acetylation and malonylation, respectively, so that the manipulation of acetyl-CoA and malonyl-CoA by ACC1 can also markedly influence the profile of protein post-translational modifications, resulting in alternated biological processes in mammalian cells. In the review, we summarize our understandings of ACCs, including their structural features, regulatory mechanisms, and roles in diseases. ACC1 has emerged as a promising target for diseases treatment, so that the specific inhibitors of ACC1 for diseases treatment are also discussed.